Chapter 16. Strawberry Production - Vance Whitaker; Nathan S. Boyd; Natalia Peres; Johan Desaeger; Sriyanka Lahiri; Shinsuke Agehara (EDIS, 2024)
Chapter 16 of the Vegetable Production Handbook of Florida